PENGARUH WORK ENVIRONMENT DAN MOTIVASI INTRINSIK TERHADAP ACADEMIC ACHIEVEMENT - Deberina Syurfi Yunina; Khoirun Nisa; Ayu Lucy Larassaty (Pusat Riset dan Inovasi Nasional, 2023)
The reason of this study was to decide the impact of work environment and intrinsic motivation on academic achievement. The research method used is a survey, where the data collection technique is a questionnaire. Respondents were taken from Faculty of Economics students in the 2022/2023 academic year at Nahdlatul Ulama University Sidoarjo. The research sample was selected aimed at students who were working. Information collection was carried out through a survey by utilizing google forms. The investigation in this utilized used Partial Least Square (PLS) with 4.0 software. The results appear that the free factors of work environment and inborn inspiration have a critical impact on the subordinate variable scholarly accomplishment in understudies of the Faculty of Economics in the 2022/2023 academic year of Nahdlatul Ulama University of Sidoarjo. It shows that a good and conducive work environment, adequate facilities, and also positive interactions can make students' academic achievement better and get satisfactory grades. In addition, students who have motivation towards learning materials and high self-confidence in facing challenges tend to achieve higher and satisfactory academic achievement.